2010
DOI: 10.1638/2010-0046.1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii Antibodies in Captive Wild Mammals and Birds in Brazil

Abstract: In this study, serum samples of 203 animals from different locations, from zoos and breeding facilities from the north and northeast regions of Brazil, were analyzed for the presence of anti-Toxoplasma gondii antibodies by the modified agglutination test (MAT) with a cutoff of 1:25. Of the sampled animals, 184 were adult mammals of both sexes and 19 were birds. Antibodies were found in 61 of 184 mammals, and no association between sex and age of the animals and the presence of T. gondii antibodies was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
4
23
1
6
Order By: Relevance
“…The results from the present study corroborate this information about the widespread presence of antibodies against T. gondii in Brazilian wildlife in general (VITALIANO et al, 2004;ANDRÉ et al, 2010;MINERVINO et al, 2010;VITALIANO et al, 2014). In the present study, T.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results from the present study corroborate this information about the widespread presence of antibodies against T. gondii in Brazilian wildlife in general (VITALIANO et al, 2004;ANDRÉ et al, 2010;MINERVINO et al, 2010;VITALIANO et al, 2014). In the present study, T.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported the presence of antibodies to T. gondii in wild procyonids (SOGORB et al, 1977;DUBEY et al, 1993;HANCOCK et al, 2005;MINERVINO et al, 2010). The results from the present study corroborate this information about the widespread presence of antibodies against T. gondii in Brazilian wildlife in general (VITALIANO et al, 2004;ANDRÉ et al, 2010;MINERVINO et al, 2010;VITALIANO et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Trabalhos relevantes, visando o diagnóstico de T. gondii em mamíferos e aves silvestres, foram realizados no Brasil GENNARI et al, 2004;MINERVINO et al, 2010;SILVA et al, 2006;YAI, 2009 (LEITE et al, 2007;PENA et al, 2006;PIMENTEL et al, 2009;SOARES et al, 2010  Detectar a presença de fragmentos de DNA de T. gondii nas amostras de água coletadas nas duas Unidades de Conservação.…”
Section: P á G I N a | 17unclassified

Tapir Health

Ordonneau,
Fernandes-Santos,
Zimmerman
et al. 2024
Fascinating Life Sciences